Impact of meteorological parameters on growth and quality of peach (Prunus persica) cv Early Grande under subtropical condition - KOUR, GAGANPREET; WALI, V K; BAKSHI, PARSHANT; KUMAR, RAKESH; KHUSHU, M K (The Indian Journal of Agricultural Sciences, 2015)
Two years experiment was carried out to study the impact of climatic factors on growth and quality of low chilling peach [Prunus persica (L.) Batsch] cultivar, viz. Early Grande. The results reveal that plant volume of Early Grande was positively influenced by maximum and minimum temperature at P1 stage. Minimum temperature at P3 stage exerted positive impact on plant volume, while plant volume was negatively related to humidity at P2 and P3 stages. Shoot extension growth was also negatively influenced by relative humidity at P3 stage. During second year, plant volume and shoot extension growth was positively related with temperature at different phenological stages, while relative humidity exerted negative impact on plant volume and shoot extension growth. The fruit diameter showed negative relation with temperature and positive relation with relative humidity at different phenological stage during first year, however reverse trend was observed during second year. Fruit weight was positively influenced by relative humidity during both the years at different phenological stages. Minimum relative humidity at P1 stage was only factor which positively influenced TSS content during second year. Maximum and minimum relative humidity at P1 stage positively favoured the acid content in fruit of Early Grande during second year. Lastly, sugar content in fruit of Early Grande was negatively influenced by maximum and minimum temperature, while positively favoured by maximum and minimum relative humidity at P2 and P3 stages during second year.